2017
DOI: 10.1007/s13311-017-0535-x
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Treatments in Eating Disorders

Abstract: Eating disorders (EDs), including anorexia nervosa, bulimia nervosa, and binge-eating disorder, constitute a class of common and deadly psychiatric disorders. While numerous studies in humans highlight the important role of neurobiological alterations in the development of ED-related behaviors, the precise neural substrate that mediates this risk is unknown. Historically, pharmacological interventions have played a limited role in the treatment of eating disorders, typically providing symptomatic relief of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 96 publications
0
16
0
4
Order By: Relevance
“…Eating disorders are severe but inadequately treated mental illnesses, in part due to our limited understanding of underlying neurobiology of the illness as well as lack of reliable animal models that can be used for rigorous testing and development of treatment options (Lutter, 2017). As an attempt to establish a more reliable animal model of EDs, in the present study we performed extensive behavioral characterization of homozygous mice for the Hdac4 A778T missense mutation, which we previously found to be associated with the risk of developing an ED .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eating disorders are severe but inadequately treated mental illnesses, in part due to our limited understanding of underlying neurobiology of the illness as well as lack of reliable animal models that can be used for rigorous testing and development of treatment options (Lutter, 2017). As an attempt to establish a more reliable animal model of EDs, in the present study we performed extensive behavioral characterization of homozygous mice for the Hdac4 A778T missense mutation, which we previously found to be associated with the risk of developing an ED .…”
Section: Discussionmentioning
confidence: 99%
“…Eating disorders (EDs), such as anorexia nervosa (AN) and bulimia nervosa (BN), are serious mental illnesses thought to develop as a result of complex gene-environment interaction (Hinney et al, 2010;Carmichael and Lockhart, 2012;Lutter et al, 2016;Baker et al, 2017). In spite of EDs having the highest mortality rate of all mental disorders, available treatments are extremely limited, mainly due to the poor understanding of the underlying neurobiology of EDs and lack of useful animal models that can be used to develop novel treatment strategies (Lutter et al, 2016;Lutter, 2017). Among the proposed factors contributing to EDs, genetics plays a major role in the development of an ED, as family and twin studies indicate that the risk of developing an ED is 60-80% heritable (Lilenfeld et al, 1998;Strober et al, 2000;Karwautz et al, 2002;Baker et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among the 45 reviews or meta-analyses, 26 were excluded for the following reasons: 16 were overviews and/or not systematic reviews with no explicit methodology for the selection of the papers mentioned [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24], one review [25] predated the World Federation of Societies of Biological Psychiatry review, one [26] reviewed the same eight studies as a meta-analysis included [27], five focused on unpublished data, or studies that were reviewed in later papers included here [28,29,30,31,32], one mainly focused on emerging treatment research or perspectives [33], two concerned oxytocin but with no specific results in AN [34,35].…”
Section: Methodsmentioning
confidence: 99%
“…Kabir et al [6] review clinical studies that have examined efficacy of these agents in patients with bipolar disorder, schizophrenia, and drug addiction, as well as animal laboratory studies that have identified cellular events that underlie behavioral correlates of human disorders. The next article in the BPsychiatric Genomics^section, by Michael Lutter [7], shows how multiple approaches are being used to make inroads on treating very challenging patients suffering from eating disorders. Leads from advances in identifying endocrine factors controlling feeding and satiety are being integrated with clinical trials of agents already approved for safe use in other disorders.…”
mentioning
confidence: 99%
“…Furthermore, pedigree analysis has yielded identification of 2 unique genetic mutations that segregate with patients afflicted with eating disorders. Just as identification of rare familial mutations associated with Parkinson's disease has paved the way to mapping a common pathophysiology relevant to sporadic forms of the disease, the seminal findings described by Lutter [7] appear to provide a secure foothold for unraveling the pathophysiology of eating disorders with the help of transgenic mice bearing these mutations. In the last article in the BPsychiatric Genomics^section, Tomoda et al [8] provide an overview of recent advances examining the role of disrupted in schizophrenia 1 (DISC1) in a complex network of cellular signaling pathways.…”
mentioning
confidence: 99%